Proceedings of the 2008 Conference on Future Play: Research, Play, Share 2008
DOI: 10.1145/1496984.1496995
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for play in computer role-playing games

Abstract: In this paper the motivations for play in the context of single-and multi-player digital Role-Playing Games (RPGs) are examined. Survey data were drawn from respondents online and participants in a related experimental study. The results indicate that motivations for play are not simple constructs, but rather composed of multiple motivational drivers that are heavily interrelated and act in concert. Character uniqueness and Discovery & Immersion were the highest ranked motivational categories. Different levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…To our knowledge, no study has evaluated the effect of a player's sense of her narrative role on the options she selects in choice structures in an interactive narrative role-playing game. This is striking, since there is tacit agreement that roles affect players during gameplay [35,37]; our work elucidates how.…”
Section: Related and Prior Workmentioning
confidence: 72%
“…To our knowledge, no study has evaluated the effect of a player's sense of her narrative role on the options she selects in choice structures in an interactive narrative role-playing game. This is striking, since there is tacit agreement that roles affect players during gameplay [35,37]; our work elucidates how.…”
Section: Related and Prior Workmentioning
confidence: 72%
“…This suggests that players' motivations not only move them to engage with the game but also shape the way in which they engage. There have also been developments of these same ideas for role-playing games not of the MMO type [74]. It should be noted though that these results are better interpreted as correlation rather than causation.…”
Section: Starting To Playmentioning
confidence: 94%
“…Whilst a range of studies have demonstrated the situational benefits of such approaches [9][10][11], a need still exists for a fuller understanding of how the indirect nature of learning through play is best selected and applied to meet a given learning requirement. The depth of interaction, and possibility games afford for increased connection and emotional investment from users [12] can be argued as one of the primary mechanisms through which they sustain engagement and foster intrinsic motivation to play [13]. In the case where the rationale behind the selection of a game-based approach stems from its perceived ability to reach at-risk groups outside of formal or structured contact, adhering to ethical principles can be particularly challenging when seeking to compete for screen-time in a leisure context.…”
Section: Fostering Trust In At-risk Groups Through An Ethical Approachmentioning
confidence: 99%